Embroidering engineering: a case of embodied learning and design of a tangible user interface. Issue 1 (2nd January 2016) - González Rivera, Rafael A.; Cortés-Rico, Laura; Pérez-Bustos, Tania; Franco-Avellaneda, Manuel
ABSTRACT: In this paper, we reflect upon the process that frames a particular MSc final capstone project which connects communities of craft women embroiderers and an interdisciplinary team of social scientists and engineers in Colombia. We argue that capstone projects framed by participatory methodologies are characterized by embodied learning processes which in turn are shaped by a tension between that which is learnt by engineers in contact with craft communities and that which is required by engineering schools to certify the skills of engineers in the making. Methodologically, the case study is based on an ethnography of the design process and complemented by an analysis of how capstone projects are narrated by engineers in dialogue with social scientists. Through the case study, we show the different negotiations and contradictions that shape this process and the implications they have for engineering education and final capstone projects in particular.